Lost Mansions of Mississippi, Volume II - Miller, Mary Carol (Book collections on Project MUSE., 2010)
As preservationist Mary Carol Miller talked with Mississippians about her books on lost mansions and landmarks, enthusiasts brought her more stories of great architecture ravaged by time. The twenty-seven houses included in her new book are among the most memorable of Mississippi's vanished antebellum and Victorian mansions. The list ranges from the oldest house in the Natchez region, lost in a 1966 fire, to a Reconstruction-era home that found new life as a school for freed slaves. From two Gulf Coast landmarks both lost to Hurricane Katrina, to the mysteriously misplaced facades of Hernando'